Reticulocyte hemoglobin equivalent for diagnosing iron deficiency anemia in children - Susanti Lisupindan Palimbong Rungngu; Audrey Wahani; Max F.J. Mantik (Paediatrica Indonesiana, 2016)
Background The prevalence of iron deficiency anemia (IDA) remains high in Indonesian children. When anemia is detected in a patient, the physician’s task is to identify the cause, address it, provide iron therapy, and prevent recurrence. However, prevention is best done by early detection. The reticulocyte hemoglobin equivalent (Ret-He) is a direct measurement of iron level in reticulocytes recently produced in the bone marrow. The Ret-He measurement may be an early indicator of iron deficiency, as it is sensitive at the initial stage of the condition.Objective To assess for a relationship between Ret-He and IDA as well as to evaluate the usefulness of Ret-He for diagnosing IDA in children.Methods This analytic, observational study with cross-sectional approach included 50 children aged 6-12 years and was performed from November 2013 to March 2014. The subjects were divided into IDA or non-IDA groups, based on ferritin levels. A correlation analysis using logistic regression was performed and the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and odds ratio (OR) were calculated. Results were considered to be statistically significant for P values <0.05.Results A low Ret-He level was significantly associated with IDA in children (P=0.005). The Ret-He cut-off point of 27.8 pg/L had sensitivity of 43.8%, specificity 85.3%, PPV 58.3%, and NPV 76.3%, with OR 4.5 (95%CI 1.1 to 17.7).Conclusion We find a significant positive relationship between Haemoglobin (Hb) and Ret-He in children, A low level of Ret-He is associated with greater risk of IDA in children. The Ret-He has a high specificity. As such, Ret-He may be useful as a screening tool for early detection of IDA in children.